From Platforms to Online Communication Tools - Ouariach Fatima Zahra; Nejjari Amel; Ouariach Soufiane; Khaldi Mohamed (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
In e-learning, the shift from platforms to online communication tools has been significant. As education evolves towards virtual environments, learning platforms become crucial for managing courses, delivering content and assessing learners. The article focuses on various forms of online communication tools, such as discussion forums, live chats and virtual meeting rooms, and explains how these tools facilitate interaction, collaboration and active participation between learners. It also discusses potential obstacles to the integration of these tools. In this contribution, we work with the LMS platform, as the various online communication tools can be found in the LMS platform. Ultimately, the article highlights the importance of combining a robust e-learning platform with appropriate online communication tools to foster an interactive learning environment.